Conservation status and strategies for the preservation of orchids in the soconusco region of southeast Mexico - Damon, Anne (Lankesteriana: International Journal on Orchidology, 2013)
A total of 320 orchid species are registered for the biodiverse region of Soconusco in the southeastern tip of Mexico. Given certain social, political, and legal limitations, the most productive strategy for preserving and restoring populations of the various species in danger of extinction, endemic, and over-exploited has been to work directly, intensively, and long-term with communities situated within or near to the few remaining hot spots of orchid diversity and abundance. With the appropriate permits, sustainable orchid cultivation has been established in various communities. We continue with long-term research into key aspects of the biology and ecology of orchids, identification of refuge sites, and modeling of geographical distribution of species.